2020
DOI: 10.29219/fnr.v64.4364
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induction activity of polysaccharide from Lentinus edodes in H22-bearing mice through ROS-mediated mitochondrial pathway and inhibition of tubulin polymerization

Abstract: Background Lentinus edodes is a medicinal mushroom widely used in Asian countries for protecting people against some types of cancer and other diseases. Objective The objective of the present study was to investigate the direct antiproliferation activity and the antitumor mechanisms of water-extracted polysaccharide (WEP1) purified from L. edodes in H22 cells and H22-bearing mice. Design The extractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Apoptosis is programmed cell death, and ROS is critical for promoting apoptosis in response to various apoptotic stimuli ( Khan et al, 2019 ; Yang et al, 2018 ). Induction of apoptosis and targeting ROS through polysaccharide intervention is an effective way to combat tumors ( Zhang et al, 2020 , 2021 ). In this study, RTFP-1 exhibited antiproliferative activity against HepG2 cells through inducing cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is programmed cell death, and ROS is critical for promoting apoptosis in response to various apoptotic stimuli ( Khan et al, 2019 ; Yang et al, 2018 ). Induction of apoptosis and targeting ROS through polysaccharide intervention is an effective way to combat tumors ( Zhang et al, 2020 , 2021 ). In this study, RTFP-1 exhibited antiproliferative activity against HepG2 cells through inducing cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have proven that ROS are closely related to mitochondria. ROS can directly damage the integrity of the mitochondrial membrane by hyperpolarizing the mitochondrial membrane and releasing cytochrome c into the cytoplasm [53,54]. In addition, ROS can also damage mitochondrial DNA, which is related to the respiratory chain, thereby aggravating the production of ROS [55].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on anti-cancer agents considered generating high levels of intracellular ROS as a sign of induced apoptosis in the cancer cells (Simon et al, 2000;Kowaltowski et al, 2004;Lee et al, 2019;Li et al, 2020). Results of the present study showed that the cells incubated with the IOP at 50 and 100 μg/mL and stained with DCFH-DA exhibited significantly high concentrations of ROS in both cancerous cell lines in a dose-dependent manner in comparison to untreated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, treatment with IOP could disturb the redox balance in NCI-H23 and A549 cells, and hence ROS may be a key mediator, leading to mitochondrial dysfunction, protein oxidation and DNA damage in cancer cells, followed by cell death or apoptosis induced by various anticancer drugs (Xiao et al, 2013;Sahayanathan et al, 2020). Many mushroom polysaccharides have also been shown to promotes production of ROS and induce apoptosis in human cancer cells (Zhang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation